2024
DOI: 10.1063/5.0185815
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton photocurrent in wide bandgap semiconductors for nonlinear optoelectronics: Comparison of GaP, GaN/InGaN, and SiC

Chuanliang Wang,
Ahsan Ali,
Khadga Jung Karki

Abstract: Wide bandgap semiconductors are ideally suited for nonlinear optoelectronics. Because their bandgaps are larger than 2 eV, simultaneous absorption of two or more near-infrared photons is necessary to excite the electrons from the valence to the conduction band. Understanding of the processes that affect multiphoton absorption is important in the design and fabrication of optoelectronic devices. Here, we present an overview of the photocurrent response in photodetectors made from GaP, GaN, InGaN, and SiC when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…If only N -photon absorption has a significant contribution to the measured signal, then the amplitudes of the signals at all harmonics scale with the N th power of the average intensity. On the other hand, if different orders of MPA contribute, the scaling of the signals at different modulation frequencies will be different, based on which one can identify the pathways of related MPA. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If only N -photon absorption has a significant contribution to the measured signal, then the amplitudes of the signals at all harmonics scale with the N th power of the average intensity. On the other hand, if different orders of MPA contribute, the scaling of the signals at different modulation frequencies will be different, based on which one can identify the pathways of related MPA. , …”
Section: Resultsmentioning
confidence: 99%
“…The order of MPA depends on the material’s electronic structure. For example, it has been found that one-, two-, and three-photon absorptions contribute to photocurrent in gallium phosphide (GaP)-based photodetectors while only three-photon absorption contributes in indium gallium nitride (InGaN) photodetectors. …”
Section: Introductionmentioning
confidence: 99%